A implementação de uma política de comunicação organizacional integrada, estratégica e pública em uma instituição federal de ensino superior: um modelo a partir da experiência da UFSM - Prediger, Solange (2023)
For the university, it has become a matter of survival considering communication as strategic, especially public ones (such as UFSM), which depend on the legitimacy of society for their maintenance and end up assuming multiple roles that go beyond teaching. We asked ourselves how the organizational communication of the institutions will be affected in the context of a sharp decrease in investments in education because, moreover, at the same time, technological convergence requires the use of all types of media to publicize actions, generate visibility, justify the existence of universities and explain society's investment. We understand the challenge for the work and study area is to create procedures and regulations to guide communication actions focused on its diverse audiences, without neglecting the precepts of an integrated, strategic and public communication. In this respect, we understand the role of a Communication Policy. The approval and, mainly, the implementation of a CP is essential, in addition to being necessary, for the development of an integrated, public and strategic organizational communication in an Federal Higher Education Institution (IFES). Therefore, the research problem arises: what are the strategies and challenges for the implementation of a strategic and integrated organizational CP, in light of the precepts of public communication, in an IFES? Considering mainly the studies by Bueno (2009) on communication policy and, in this sense, the steps for building a CP (implantation, implementation and evaluation), we analyze how this is happening in practice. The general purpose of this study is to propose an operational model for the implementation of an integrated, public and strategic organizational CP in an IFES. The approach in this research is inductive method and the action research as a research method, which is characterized as a qualitative and exploratory study. We did a bibliographical research on the subject and, later, from the questionnaire, we verified which IFES have CP approved. Through document search, we analyzed the PCs and websites of institutions that had the approved document, including UFSM. Based on in-depth interviews and participant observation, we describe the CP construction process at UFSM and present the strategies and challenges encountered in the institution's CP implementation. Consequently, by the end, we will have the model, with a significant range of actions that can be developed at UFSM to improve the CP implementation process and serve as a basis for the discussion on the construction of the CP in other institutions.